Pengaruh Gaya Kepemimpinan, lingkungan Kerja, Dan Keselamatan Kerja Terhadap Kinerja Karyawan (Studi Pada Karyawan CV. Unit Clean Industry Pasuruan) - Cyndi Khoryratu Hikmah; Abdul Kodir Djaelani; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the factors that influence employee performance. These factors are leadership style, work environment, and work safety. This research study on the performance of CV employees. Pasuruan Clean Industry Unit. CV. Unit Clean Industry is a household cleaning equipment company with various types of equipment such as floor mops, other brushes, and other cleaning tools. The purpose of this study was to determine the influence of leadership style, work environment, and work safety on employee performance. Data were analyzed using quantitative methods by distributing questionnaires. The sample in this study were 47 respondents and data processing using SPSS. The analytical tools used in this research are validity test, reliability test, classic assumption test, multiple linear regression analysis, hypothesis test, and adjusted R square test. This research has fulfilled the validity test and reliability test. The results of testing the first hypothesis (H1) are accepted that leadership style, work environment, and work safety have a significant positive effect on employee performance with a significance level of 0.000. The second hypothesis (H2) is accepted which shows that there is a significant positive effect between leadership style on employee performance with a significance level of 0.031. The third hypothesis (H3) is accepted which indicates that there is a significant positive effect between the work environment on employee performance with a significance level of 0.001. The fourth hypothesis (H4) is accepted which indicates that there is a significant positive effect of work safety on employee performance with a significance level of 0.001. The results of this study concluded that the variables of leadership style, work environment, and work safety have both a simultaneous and partial effect on employee performance Keywords : Employee Performance, Leadership Style, Work Environment, And Work Safety